Concretos com misturas de agregado residual de construção e demolição (RCD) e pozolana, com ênfase na carbonatação - Santos, Cristiane Carine dos (2017)
Among the numerous environmental impacts caused by the various segments of the economy, civil construction stands out as one of the sectors that consumes the most natural resources and generates emissions to the environment, encouraging researchers to carry out studies to find ways to minimize these impacts. Therefore, the present research aims to study different pillar alternatives, composed of two types of cement (CP IV and CP V-ARI), pozolana (rice husk ash) and construction and demolition residues (RCD), to enable determination of the main environmental impacts generated by each one of them and to define what will be the best alternative being evaluated environmentally and economically. The proportions of the mixtures of each pillar were defined, tests of resistance to axial compression, modulus of longitudinal elasticity and durability (accelerated carbonation) were carried out. In that the resistance of the pillars with substitutions of natural aggregates by the RCD decreased considerably, but with the use of pozolana a compensation of this fall was obtained. A similar process was observed with the modulus of elasticity test. In relation to the durability, the higher carbonation coefficients were obtained by the pillars in which CPIV cement was used, with an increase according to the increase of the substitution of the natural aggregate by the RCD. However, the pillars with CPV-ARI and 15% and 30% RCD did not present carbonation in any of the analyzed ages, which can be explained by the influence of the low water / cementitious materials ratio for these two traits, since the dimensioning occurred in equality of resistance. Regarding the Life Cycle Assessment, with a "cradle to grave" approach, the pillars with the CPIV cement were not favorable with replacements of natural aggregates by the RCD, whereas the compounds by the CPV-ARI obtained better results when compared to the impacts generated by the reference pillar (without substitutions). When performing the sustainability integration x cost, the pillar with 15% RCD and CPV-ARI cement was obtained as the best alternative.